Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1172/jci112708
|View full text |Cite
|
Sign up to set email alerts
|

Na+ transport in cystic fibrosis respiratory epithelia. Abnormal basal rate and response to adenylate cyclase activation.

Abstract: The transepithelial potential difference (PD) of cystic fibrosis (CF) airway epithelium is abnormally raised and the Cl-permeability is low. We studied the contribution of active Na' absorption to the PD and attempted to increase the Cl-permeability of CF epithelia. Nasal epithelia from CF and control subjects were mounted in Ussing chambers and were short-circuited. The basal rate of Na' absorption was raised in CF polyps compared with control tissues. Whereas beta agonists induced Cl-secretion in normal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
238
1
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(260 citation statements)
references
References 32 publications
(41 reference statements)
19
238
1
2
Order By: Relevance
“…Although regulatory pathways that involve cyclic AMP and Ca2+ phospholipid-dependent protein kinases are defective in CF airway epithelium (Boucher et al, 1986), a recent report indicates that Ca2+-dependent Cl-secretory regulatory mechanisms are retained by CF epithelia . Our data show [Ca21]i was increased and CPsecretion stimulated by ATP and UTP in CF airway epithelial cells pretreated with amiloride.…”
Section: Discussionmentioning
confidence: 99%
“…Although regulatory pathways that involve cyclic AMP and Ca2+ phospholipid-dependent protein kinases are defective in CF airway epithelium (Boucher et al, 1986), a recent report indicates that Ca2+-dependent Cl-secretory regulatory mechanisms are retained by CF epithelia . Our data show [Ca21]i was increased and CPsecretion stimulated by ATP and UTP in CF airway epithelial cells pretreated with amiloride.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Electrolyte transport defects in the CF airway epithelium have been extensively characterized in CF nasal epithelia, both in vitro and in vivo. [44][45][46] Such studies have demonstrated that, in addition to a defective cAMP inducible chloride secretory response, CF nasal epithelia have increased levels of amiloride-sensitive Figure 2 Model for cellular compartmentalization of CFTR expression and function in the airway. The level of CFTR expression in the airway is highly regulated within different cell types.…”
Section: Cftr Is An Apical Membrane Chloride Channel and Regulator Ofmentioning
confidence: 99%
“…Indeed, only after Na þ transport is down-regulated or inhibited with amiloride is it possible to observe Cl 2 secretion in normal cells. It is generally accepted that the difference in V ap between normal and CF cells is due to the loss of CFTR channels and the higher Na þ permeability in CF cells (Boucher et al 1986(Boucher et al , 1988Boucher 1994a,b). Besides Cl 2 , CFTR also conducts HCO 3 2 , as shown in the studies of Gray et al (1990) and Linsdell and coworkers (Linsdell et al 1997;Tang et al 2009;Li et al 2011) and more recently by Ishiguro et al (2009).…”
Section: Airway Cells Secrete Bicarbonatementioning
confidence: 99%